The irrigation advisory plan of Campania region: from research to operational support for the water directive in agriculture - D'Urso G.; D'Antonio A.; Vuolo F.; De Michele C. (Irrigation in Mediterranean agriculture: challenges and innovation for the next decades, 2008)
The Irrigation Advisory Plan of Campania Region is an initiative of the Assessor for Agriculture and Productive Activities, through the Research and Development Service (Se.S.I.R.CA); it consists of an innovative advisory service for irrigation, based on the combined use of Earth Observation data, GIS and Information Technology to provide crop water requirements information from the field scale (>1 ha) to the irrigated basin scale (3000 ha). This initiative, which is perfectly aligned with the recommendations of European Union through the Water Directive n. 60/2000 has been tailored to improve the water use efficiency not only at farm level, but also at the district scale, with tangible benefit for the economy of primary sector and environmental protection. The personalized information provided to farmers and irrigation managers consist of the maximal irrigation volumes to be applied on a weekly basis and the duration of irrigation. This information is sent within 36 hours from the satellite acquisition to each farmer via SMS, MMS and E-mail; in addition a dedicated Web-GIS has been developed to monitor irrigation advice at district level.
International Conference on Irrigation in Mediterranean Agriculture: Challenges and Innovation for the Next Decades, 2008/06/17-18, Naples (Italy)